2022
DOI: 10.3390/nu14102061
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Pilot Study to Evaluate the Impact of Salbi Educa Nutrition App in Macronutrients Intake and Adherence to the Mediterranean Diet: Randomized Controlled Trial

Abstract: Promoting a healthy diet is a relevant strategy for preventing non-communicable diseases. This study aims to evaluate the impact of an innovative tool, the SAlBi educa nutrition app, in primary healthcare dietary counseling to improve dietary profiles as well as adherence to the Mediterranean diet. A multi-center randomized control trial comprising 104 participants was performed. Both control (n = 49) and intervention (n = 55) groups attended four once-weekly sessions focusing on healthy eating habits and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The results of the present study, in line with the results obtained by Alonso-Dominguez et al, have shown a significant improvement in both the ADM index and the proportion of participants that achieved high compliance (MDSS ≥ 9) among the participants (university students) who used ‘feedback’ e-12HR (IG) compared to the participants who used ‘non-feedback’ e-12HR (CG). Furthermore, this improvement was observed over shorter follow-up periods than in other studies [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The results of the present study, in line with the results obtained by Alonso-Dominguez et al, have shown a significant improvement in both the ADM index and the proportion of participants that achieved high compliance (MDSS ≥ 9) among the participants (university students) who used ‘feedback’ e-12HR (IG) compared to the participants who used ‘non-feedback’ e-12HR (CG). Furthermore, this improvement was observed over shorter follow-up periods than in other studies [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 54%
“…Another study carried out by Gonzalez-Ramirez et al [ 42 ], who also used a smartphone app with certain similarities to e-12HR, showed that the ADM score was significantly enhanced at month 3 with 1.4 points of improvement (intervention group only—no control group-).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feedback from the dietitians was positive, and 4/5 dietitians reported that the weekly MDA score could motivate the users towards a healthier lifestyle. In another pilot study 36 that took place in Spain, participants were recruited to use a nutritional education app that offers MD-based dietary counseling. It was found that the participants had a significant increase in carbohydrate intake and a significant decrease in fat intake in a period of one month and improved their dietary habits significantly in three months.…”
Section: Discussionmentioning
confidence: 99%
“…Food Frequency Questionnaires (FFQs) are inexpensive and probably one of the most commonly used dietary tools for self-assessment. Therefore, several applications incorporate FFQs to monitor dietary habits [ 1 , 2 ]. For example, Fondazione Bruno Kessler developed the Lifestyle Behaviour Change (LBC) application to offer people from the Trentino region an application to self-monitor several aspects of a healthy lifestyle, with nutrition habits being one of them.…”
Section: Introductionmentioning
confidence: 99%